Modeling and analysis of LTE connectivity in a high mobility vehicular environment. (May 2018) - Burbano-Abril, A.; Edwards, R.M.; Rangel-Licea, V.; Aquino-Santos, R.; Lopez-Guerrero, M.; Kalawsky, R.S.; Behjati, M.
Abstract: Long-Term Evolution (LTE) technology has several features that make it an attractive alternative to be used in vehicle-to-infrastructure communications for intelligent transportation systems. However, before LTE can be widely used in this context, a number of analyses must provide convincing evidence that critical network functions (e.g. resource allocation strategies) yield adequate performance. To this end, in this work, we introduce a Markov-chain based model for LTE downlink channel quality, a prime factor affecting performance. Our model comes from the analysis of a large number of measurements of LTE Cell-Specific Reference Signals that were collected through a crowdsourcing application on a motorway in the UK. The model is intended to be used in performance evaluation studies and we exemplify its use with a case study, where we estimate the downlink transmission capacity of an LTE network. We also discuss other potential applications.